2023
DOI: 10.1101/2023.06.23.546277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The metabolic role of vitamin D in children’s neurodevelopment: a network study

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with various proposed environmental risk factors and a rapidly increasing prevalence. Mounting evidence suggests a potential role of vitamin D deficiency in ASD pathogenesis, though causal mechanisms remain largely unknown. Here, we investigate the impact of vitamin D on child neurodevelopment through an integrative network approach that combines metabolomic profiles, clinical traits, and neurodevelopmental data from a pediatric cohort. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…In addition, there is uncertainty around the definition of vitamin D insufficiency or deficiency, 74 particularly for neurodevelopment, 14 as well as lack of clearly defined underlying mechanisms through which vitamin D influences neurodevelopment. [12][13][14][15][16][17][18][19][20][21][22] Even the most recent Cochrane review of vitamin D in pregnancy identified 30 trials in over 7000 women (without reporting child neurodevelopment) and found the quality of evidence to be moderate to very low. 75 Future studies should focus on sufficiently large (powered) samples of vitamin D-deficient populations to verify that low vitamin D in pregnancy does not pose a threat to child neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is uncertainty around the definition of vitamin D insufficiency or deficiency, 74 particularly for neurodevelopment, 14 as well as lack of clearly defined underlying mechanisms through which vitamin D influences neurodevelopment. [12][13][14][15][16][17][18][19][20][21][22] Even the most recent Cochrane review of vitamin D in pregnancy identified 30 trials in over 7000 women (without reporting child neurodevelopment) and found the quality of evidence to be moderate to very low. 75 Future studies should focus on sufficiently large (powered) samples of vitamin D-deficient populations to verify that low vitamin D in pregnancy does not pose a threat to child neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some evidence from observational animal and human studies suggests a role of vitamin D for neurodevelopment and functioning, although findings are inconclusive and specific underlying mechanisms driving the association are not well established. [12][13][14][15][16][17][18][19][20][21][22] A number of cohort and case-control studies have reported associations between low vitamin D in pregnancy and/or childhood and increased risk of behaviour problems such as Autism Spectrum Disorder and Attention Deficit Hyperactivity. [23][24][25][26][27] Two reviews of trials of vitamin D supplementation for children with attention-deficit/hyperactivity disorder also found a small decrease in symptoms, although authors noted the quality of evidence was low.…”
mentioning
confidence: 99%